Pola Pembelajaran Pendidikan Agama Hindu Di Utama Widya Pasraman Sila Kertha Raharja Jembrana - Trisna Yanti, Ni Komang Erni; Suwendra, I Wayan (Jayapangus Press, 2022)
Education is the most important priority in a country in order to improve the nation's intelligence and good morals. In Indonesia, education has been prioritized with 9 years of compulsory education in order to eradicate ignorance and poverty, with an intelligent society and noble morals that can guarantee a better life. Considering the importance of education and learning patterns for the younger generation. The existence of schools with Hindu nuances is to maintain the continuity of Hinduism in the future. The presence of Utama Widya Pasraman Sila Kertha Raharja in Jembrana as a school with a Hindu nuance can answer the needs of the Hindu community for education based on Hindu religious teachings. Utama Widya Pasraman Sila Kertha Raharja aims to instill in children a sense of love for the religion they adhere to, namely Hinduism as an implementation of Tri hita karana. This research uses a qualitative approach method. Qualitative research is research that is descriptive in nature and tends to use analysis. UWP Jembrana is a pasraman with Hindu religious auspices. The high school that was founded by Pasraman and pioneered from the beginning until now is still in the process of adding buildings to be erected at the school. The learning pattern applied at UWP Jembrana is predominantly taught material related to religion such as ethics, morality, tattwa, yoga, Kawi language, etc. In extracurricular activities, students will be divided into two groups, namely the male student group and the female student group.